Beyond monoclonal antibodies: constraints and the case for alternative PD-1/PD-L1-targeting formats - Porozova, Natalia O.; Petukhova, Natalia V.; Gureev, Maxim A.; Moiseev, Ivan S.; Eliseev, Igor E.; Fedorova, Ludmila V.; Porozov, Yuri B. (Frontiers in Immunology, 2025)
Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) blockade has reshaped immuno-oncology, with antibodies establishing benchmarks for survival and durability of response across multiple tumor types. Yet format-related constraints of monoclonal antibodies persist, including incomplete and heterogeneous intratumoral penetration, long half-life with limited real-time toxicity control, immune-related toxicities, and context-dependent resistance within the tumor microenvironment. This Review synthesizes the current landscape and near-term prospects of complementary or alternative modalities for PD-1/PD-L1 pathway control. Within antibody-based approaches, we first consider clinical combinations of classical PD-1/PD-L1 antibodies and then review bispecific antibodies that integrate blockade with co-inhibition or context-dependent co-stimulation, reduced-size antibody scaffolds with tunable pharmacokinetics and diffusion, Fc-engineered formats to modulate effector functions, and locally delivered or gene-encoded fragments that intensify intratumoral exposure. Beyond conventional antibodies, we appraise non-antibody biologics and small-molecule agents, including small molecules that promote PD-L1 dimerization to occlude the PD-1 interface, as well as decoy receptors and aptamers, and delivery-focused strategies that enable spatially constrained or vectorized pathway modulation. Across these modalities, we emphasize fit-for-context design that links target biology to the physicochemical profile of each format and route of administration, and we consolidate evidence from preclinical to late-phase settings. Building on prior reviews that have cataloged clinical outcomes of PD-1/PD-L1 antibodies and provided in-depth overviews of individual emerging modalities, this article adopts a format-centered, cross-modality conceptual framework that connects antibody-intrinsic and microenvironmental constraints to the design and emerging clinical positioning of alternative PD-1/PD-L1-targeting modalities, to clarify when and how intensification or format switching is most likely to be beneficial. We conclude that PD-1/PD-L1 antibodies retain a foundational role, while additional modalities are positioned to serve as complementary or alternative options that mitigate inherent physical and biological limitations when matched to the spatial, cellular, and pharmacological constraints of individual tumors.